Utility of CT Perfusion Imaging in Patients With Vertebral Artery Stenosis Treated With Balloon Expandable Stent - Wei, Wei; Song, Chong; Li, Xuqin; Jin, Dianshi (Frontiers in Neurology, 2021)
Objective: To investigate the clinical value of CT perfusion (CTP) imaging in vertebral artery stenosis stenting, so as to provide the basis for preoperative and postoperative evaluation. Ninety-seven patients with vertebral artery stenosis were accepted for endovascular stenting between Jan 2016 and Jan 2020. CT angiography, Digital Subtraction Angiography, and CTP were performed pre-operation and post-operation. The cerebral blood volume (CBV), cerebral blood flow (CBF), and mean transmit time (MTT) between the health and affected sides were analyzed statistically, and the imaging results pre- and post-operation were evaluated. The stenosis was relieved by endovascular stents in all 97 patients without serious complications. The abnormal perfusion was observed in 66 patients (68%). The differences in CBF and MTT between the diseased side and healthy side were statistically significant (P < 0.05). Compared with the preoperative imaging, the postoperative CTP was improved in 59 patients (89%). The differences in CBF and MTT between pre-operation and post-operation were statistically significant (P < 0.05). But there was no significant difference in CBV. CTP can sensitively reflect the perfusion of brain, and can also be used for preoperative and postoperative evaluation of vertebral artery stenting. It may be helpful as an adequate indicator of vertebral artery stenosis stent surgery.